Título Padrão - Santos, Fabiana Pereira dos (Informação em Pauta, 2021)
The world of work has gone through changes, and professionals are in constant need of continuing education. To improve the provision of services and value professionals, the State encourages and even formulates instruments to facilitate the management of the career of it employees.One of the instruments is the career plan for Technical-Administrative positions in Education, established by law 11.091, of 12/01/05. The goal is to investigate the "uses of self" made by librarians in their work activities after their continuing education in stricto sensu post-graduation courses. The study will be based on ergology theories. This proposal is justified by the importance of studying a professional practice that has historical ballast, is regulated and established in the world of work. It is believed that professionals use strategies to perform renormalizations, and thus understand and dribble the deformations of the environment and give meaning to their activities. And that continuing education at the master's and doctoral levels can be used as tools that will support and help these actions. These are postulates inspired by the theoretical review carried out and are important for the development of empirical research, which was proposed to be carried out with librarians who work in the federal public service.